2020
DOI: 10.1002/mnfr.202000566
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GG and Oat Beta‐Glucan Regulated Fatty Acid Profiles along the Gut‐Liver‐Brain Axis of Mice Fed with High Fat Diet and Demonstrated Antioxidant and Anti‐Inflammatory Potentials

Abstract: Scope This study takes a novel approach to investigate the anti‐inflammatory and antioxidant effects of prebiotic oat beta‐glucan (OAT) and the probiotic Lactobacillus rhamnosus GG (LGG) against high‐fat diets (HFD) by examining the fatty acid profiles in the gut‐liver‐brain axis. Method and Results HFD‐fed C57BL/6N mice are supplemented with OAT and/or LGG for 17 weeks. Thereafter, mass spectrometry‐based targeted lipidomics is employed to quantify short‐chain fatty acids (SCFA), polyunsaturated fatty acids (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Our results showed that Bacillus toyonensis SAU-19 and SAU-20 reduced the MDA levels and increased the SOD, CAT, and GSH activity in the serum. This result is consistent with a previous study by Yau et al (2020) which reported that, Lactobacillus rhamnosus GG could improve the antioxidant capacity of mice fed high fat diet.…”
Section: Discussionsupporting
confidence: 94%
“…Our results showed that Bacillus toyonensis SAU-19 and SAU-20 reduced the MDA levels and increased the SOD, CAT, and GSH activity in the serum. This result is consistent with a previous study by Yau et al (2020) which reported that, Lactobacillus rhamnosus GG could improve the antioxidant capacity of mice fed high fat diet.…”
Section: Discussionsupporting
confidence: 94%
“…In general, the majority of these studies have addressed the effects of specific probiotic strains in animals challenged by diets leading to NAFLD. In this line, the administration of several probiotic strains (mainly Lactobacillus and Bifidobacterium ) has been shown to be effective in reducing liver lipid accumulation under dietary conditions providing 40 to 65% of energy as fat [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Moreover, this effect is also maintained when excessive hepatic lipid accumulation is mediated by dietary conditions providing high sugar intakes (10 to 30% of energy as fructose).…”
Section: Effects Of Probiotic Administration (Single Strain and Mixtu...mentioning
confidence: 99%
“…A number of studies showed that L. rhamnosus GG had remarkable effects on inflammation and infection [15,16]. Whether LGG-EVs have anti-inflammatory effects on colitis remains unknown.…”
Section: Rhamnosus Gg-derived Evs Alleviated Dss-induced Colitismentioning
confidence: 99%